Adenomas per colonoscopy and adenoma per positive participant as quality indicators for screening colonoscopy - Wang, Shuo; Kim, Adam S.; Church, Timothy R.; Perdue, David G.; Shaukat, Aasma (Endoscopy International Open, 2020)
Background and study aims Adenomas per colonoscopy (APC) and adenomas per positive patient (APP) have been proposed as additional quality indicators but their association with adenoma detection rate (ADR) is not well studied. The aim of our study was to evaluate the variability in APC and APP, their association with ADR, and associated risk factors in screening colonoscopies from a community practice.Patients and methods We calculated the APC, APP, and ADR from all screening colonoscopies performed over 5 years. We used adjusted hierarchical logistic regression to assess the association of factors with APC, APP, and ADR.Results There were 80,915 screening colonoscopies by 60 gastroenterologists. The median (Q1-Q3) APC, APP, and ADR were 0.41 (0.36 – 0.53), 1.33 (1.23 – 1.40), and 0.32 (0.28 – 0.38), respectively. Despite the high correlation between APC and ADR, 47.6 % of endoscopists with the lowest APC had a higher ADR, and no endoscopists with the highest APC had a lower ADR. Of endoscopists with the lowest APP, 74.3 % had a higher ADR and 5.6 % of endoscopists with the highest APP had a lower ADR. Factors associated with higher APC after multivariable adjustment included: older patients age (OR 1.003; 95 % CI 1.002 – 1.005), male patients (OR 1.123; 95 % CI 1.090 – 1.156), younger endoscopist age (OR 0.943; 95 % CI 0.941 – 0.945), and longer withdrawal time (OR 3.434; 95 % CI 2.941 – 4.010). Factors associated with higher APP were male sex, younger endoscopist age, and longer withdrawal time.Conclusion APC and APP provides additional information about endoscopist performance. Younger endoscopist age and longer withdrawal time are associated with colonoscopy quality.